Nutrient content evaluation of dried poultry waste urea molasses block (DPW-UMB) on In-vitro analysis - Danung Nur Adli; Osfar Sjofjan (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2018)
The research purpose was to determine nutrient content of dried of poultry waste urea molasses block (DPW-UMB). The research method was used completely randomized design with 3 treatments and 5 replicates. The treatments used for research were T1 (10% manure of laying chicken and 25% molasses), T2 (15% manure of laying chicken and 30% molasses), and T3 (20% manure of laying chicken and 30% molasses). The data analysis was the analysis of variance (anova) and continued by Duncan Multiple Range Test. The results showed that treatments has significantly difference (P<0.01) on dry matter, crude protein, and ash. It could be concluded that dpw-umb contained sufficient levels of nutrients. it could be used as feedstuff for ruminants for supplementation with the required nutrients.